Penerapan Model Pembelajaran Mastery Learning Untuk Meningkatkan Prestasi Belajar Matematika Siswa Kelas IV SD Negeri 2 Seraya Barat - Ni Kadek Suartini (Jayapangus Press, 2019)
The background of this research is because the mathematics learning achievement of fourth grade students of SD Negeri 2 Seraya Barat in Semester I in 2018/2019 is still low. Student achievement is still far from the criteria set by the school. To overcome these problems the authors make changes to the learning process by applying the mastery learning learning model to improve mathematics learning achievement of fourth grade students of SD Negeri 2 Seraya Barat in the first semester of the 2018/2019 academic year. This research is a classroom action research that aims to improve mathematics learning achievement. Subjects in the study were fourth grade students in semester 1 of SD Negeri 2 Seraya Barat and 7 female students. Data collected in this study are student achievement data obtained through student achievement tests at the end of the cycle. Student achievement data is then analyzed using quantitative descriptive data analysis to determine the average student achievement and the percentage of students' mastery learning. From the results of research conducted, an increase in student achievement from the initial conditions to the first cycle and second cycle. The average student learning achievement at the beginning of the cycle is 60.00 with a sufficient category, while classical learning completeness reaches 42.86%. In the first cycle, the average student learning achievement was 69.29 with quite good category and mastery learning reached 64.29%. While in the second cycle the average student learning achievement reached 75.00 with good category and mastery learning reached 85.71%. From the results of this study, it can be concluded that the application of the mastery learning model can improve mathematics learning achievement of fourth grade students of SD Negeri 2 Seraya Barat in the first semester of the 2018/2019 academic year.